The Nose as a Route for Therapy: Part 1. Pharmacotherapy - Cingi, Cemal; Bayar Muluk, Nuray; Mitsias, Dimitrios I.; Papadopoulos, Nikolaos G.; Klimek, Ludger; Laulajainen-Hongisto, Anu; Hytönen, Maija; Toppila-Salmi, Sanna Katriina; Scadding, Glenis Kathleen (Frontiers in Allergy, 2021)
This article reviews nasal structure and function in the light of intranasal pharmacotherapy. The nose provides an accessible, fast route for local treatment of nose and sinus diseases, with lower doses than are necessary systemically and few adverse effects. It can also be used for other medications as it has sufficient surface area protected from local damage by mucociliary clearance, absence of digestive enzymes, responsive blood flow and provides a rapid route to the central nervous system.